Canadian Association of Radiologists Prostate MRI White Paper. Issue 4 (November 2022) - Chang, Silvia D.; Reinhold, Caroline; Kirkpatrick, Iain D. C.; Clarke, Sharon E.; Schieda, Nicola; Hurrell, Casey; Cool, Derek W.; Tunis, Adam S.; Alabousi, Abdullah; Diederichs, Brendan J.; Haider, Masoom A.
Prostate cancer is the most common malignancy and the third most common cause of death in Canadian men. In light of evolving diagnostic pathways for prostate cancer and the increased use of MRI, which now includes its use in men prior to biopsy, the Canadian Association of Radiologists established a Prostate MRI Working Group to produce a white paper to provide recommendations on establishing and maintaining a Prostate MRI Programme in the context of the Canadian healthcare system. The recommendations, which are based on available scientific evidence and/or expert consensus, are intended to maintain quality in image acquisition, interpretation, reporting and targeted biopsy to ensure optimal patient care. The paper covers technique, reporting, quality assurance and targeted biopsy considerations and includes appendices detailing suggested reporting templates, quality assessment tools and sample image acquisition protocols relevant to the Canadian healthcare context.